Limb salvage surgery in extreme situations of prosthetic complications - Freitas, J (2017)
The treatment of periprosthetic hip and knee infection associated with loss of bone substance, as well as the treatment of the infection of large structural allografts used in tumoral reconstructive surgery, are a major challenge to the orthopaedic surgeon. Indeed, these are chronic conditions which are submitted to multiple surgeries and prolonged antibiotic therapy in socially and professionally vulnerable patients. Many of these cases receive proposals for limb amputation/disarticulation or extraction of the prosthesis without structural reconstruction aggravating, even more, their suffering and functional disability. The aim of this study is to show the results of a treatment of complex hip and knee periprosthetic infections and of a structural allograft, in the context of limb salvage surgery. 9 patients were treated, minimum age of 22 years and maximum of 76 years with multiple surgeries and from different national hospitals. Six of these patients had periprosthetic infection of the hip and knee (primary, revision and tumoral prostheses) and two of the patients showed an apparent allergic reaction to metal/iodine. The remaining case, an infection of a large femoral structural allograft, used in tumoral surgery. The main cause of the infection was the St. aureus multiresistant. One of the patients showed multimicrobial multiresistant flora. Treatment consisted in 2 different operative stages. First stage (7 to 9h): Extraction of the prosthesis or allograft; debridement and extensive excision of the periprothetic infected and devitalized bone and soft tissue, a minimum thickness of 4 mm; pulsatile lavage of the bleeding “surgical bed” with betadine / H2O2 and saline; implantation of large methyl methacrylate with gentamicin spacer. Triple intravenous antibiotic therapy was made for 8 to 9 weeks, with rigorous analytical control, and some of the patients were able to walk with the support of axillary support crutches. The second surgical stage (5 to 7h) takes place after normal levels of PCR: spacer excision with prosthetic joint reconstruction in 8 cases and in one case a silver coated knee arthrodesis prosthetic implant (bactericidal effect). So, 3 silver coated total femoral prostheses and 5 silver coated total hip prostheses, with the reconstruction of the proximal half of the femur, were applied. The interventions took place between July 2014 and April 2016. Patients were discharged after being able to walk with the help pf crutches and kept taking oral antibiotics until the normalization of PCR in 3 consecutive analytical assessments spaced by 15 days. After a clinical/ analytical evaluation, all patients showed a normal PCR, without pain and without signs of infection and/or active fistulas. Currently 5 patients walk without external support. The oldest case has 28 months of follow-up and all have a minimum follow-up of 7 months, average of 17,5 months. All patients expressed great satisfaction with the outcome of the surgical procedures for the preservation of their lower limbs. Chronic relapsing, multidrug-resistant, periprosthetic infection should be treated aggressively in a combination of surgical techniques of prosthetic revision and tumoral surgery, first through an extended debridement of devitalized tissue and the extraction of the prosthesis with the appropriate antibiotic therapy; second, with the reconstruction of the bone loss with silver coated modular prostheses, which are indicated in order to prevent the mutilating surgery and provide the restoration, as much as possible, of the functional capacity. The results obtained have been very satisfactory, although the follow-up time is insufficient to draw definitive conclusions about the infectious relapse. Such limb salvage surgery is indicated for the treatment of complex clinical situations as an alternative to the disarticulation / limb amputation, i.e. supports the hope of curing clinical and surgical situations that many surgeons designate by horrendoplasties.